1995
DOI: 10.1002/pola.1995.080331424
|View full text |Cite
|
Sign up to set email alerts
|

A Nd‐carboxylate catalyst for the polymerization of 1,3‐butadiene: The effect of alkylaluminums and alkylaluminum chlorides

Abstract: The ternary neodymium‐based catalyst for the polymerization of 1,3‐butadiene, Nd(versatate)3/Ali‐Bu2H/tert‐butyl chloride, has been examined with respect to the effects of a range of alkylaluminums and alkylaluminum chlorides. Using either pre‐formed or in situ catalysts, observations pertaining to catalyst activity and physical state and the characteristics of the final polymer are discussed. The catalyst activity series with the type of alkylaluminum was found to be: Aln‐Pr3 ≫ Aln‐Dodec3 = Aln‐Oct3 = Aln‐Hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
3
11
0
4
Order By: Relevance
“…14 Some research has shown that REs have a very strong inductive effect on polymers, 15,16 and some properties of polymers are enhanced by the addition of REs. 17 Unlike other modifiers, REs can improve polymer properties in small amounts.…”
Section: Introductionmentioning
confidence: 99%
“…14 Some research has shown that REs have a very strong inductive effect on polymers, 15,16 and some properties of polymers are enhanced by the addition of REs. 17 Unlike other modifiers, REs can improve polymer properties in small amounts.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, catalisadores de interesse prático são obtidos somente se um doador de cloro estiver presente no sistema catalítico [5] . Atualmente, o sistema catalítico à base de neodímio mais utilizado comercialmente é constituído por Nd(carboxilato) 3 /haletos de alquilalumínio ou haletos orgânicos/alquilalumínio, preparados em um solvente do tipo hidrocarboneto [6] . O modo de preparo do catalisador exerce grande influência sobre a natureza física, a atividade catalítica, a massa molar e a distribuição da massa molar do polímero.…”
Section: -Avaliação Das Condições De Envelhecimento Do Sistema Catalíunclassified
“…Com relação à microestrutura, o t-BuCl, forneceu um maior teor de unidades 1,4-cis, seguido pelo EASC e pelo DEAC, respectivamente. Esses resultados não estão de acordo com a literatura [8,12] , segundo a qual o agente de halogenação não altera a microestrutura do polibutadieno. Entretanto, cloretos de alquilalumínio do tipo R x Al y Cl z , atuam tanto como agentes de alquilação como agentes de halogenação, sendo assim, o DEAC por ter um maior poder de alquilação em relação ao EASC concorre de maneira mas eficaz pela vacância do átomo de neodímio, favorecendo a inserção 1,4-trans e, conseqüentemente, diminuindo o teor de unidades 1,4-cis [2] .…”
Section: Agradecimentosunclassified
“…A produção de polidienos estereorregulares depende tanto de fatores relacionados ao sistema catalítico quanto aos parâmetros da polimerização [4] . Há vários estudos na literatura [3][4][5][6][7][8]11,12] sobre sistemas catalíticos ternários, constituídos por um sal de neodímio, um agente de alquilação e um agente de halogenação. Assim, este trabalho tem por objetivo avaliar a Resumo: Neste trabalho foi utilizado um sistema catalítico composto por hidreto de diisobutilalumínio (DIBAH), versatato de neodímio (NdV) e um agente de cloração para avaliar a influência da fonte de cloro e da razão molar Cl:Nd nas características da reação de polimerização (conversão e constante de velocidade de propagação) e do polibutadieno (massa molecular e microestrutura).…”
Section: Introductionunclassified